Influencia del clima laboral y la motivación en el desempeño del personal de la empresa TelAndNet Solution S.A.C., Trujillo, 2021 - Córdova Huamán, Jessica Marilyn (2022)
This research was developed with the purpose of determining how the work environment and motivation influence the performance of the staff of the company TelAndNet Solution S.A.C., City of Trujillo, year 2021. It is a non-experimental descriptive-correlational research and the sample was considered to be 33 workers of the company. For data collection, an interview was applied to the manager and the interview guide instrument with a total of 13 questions. Likewise, the survey and the questionnaire instrument with a total of 36 questions were used, its reliability was measured through the Cronbach coefficient and the following were obtained: the work environment variable 0.937, motivation 0.904 and performance 0.874. In addition, documentary analysis was used to collect information regarding the daily work of the staff, data collected in 2021 to measure their performance. Finally, with this study it was concluded that the work environment and motivation positively influence the performance of the staff of the company TelAndNet Solution S.A.C., City of Trujillo, year 2021. The correlation found in the SPSS version 25 program was positive, therefore, if the level of work environment and motivation increases, staff performance will increase; however, the results show that the company has a medium level of work environment, a regular level of motivation and a high level of performance, therefore, it is recommended to improve work environment and motivation to maintain or improve staff performance.